High-concentration salt-based conductive gel as well as preparation method and application thereof

By using a high-concentration salt solution with strong hydration ability as the dispersed phase, a flexible conductive hydrogel is prepared with low modulus, high-strength and low mechanical hysteresis, the problem of insufficient mechanical parameters of existing conductive gel strain sensors is solved, and a more stable and reliable electrical signal output is achieved.

CN119874976APending Publication Date: 2025-04-25CHENGDU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510174620.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The mechanical parameters such as modulus, strength and mechanical hysteresis of existing conductive gel strain sensors fail to meet the usage requirements well, resulting in problems such as low signal-to-noise ratio of the output electrical signal, missing local signals, and narrow signal detection threshold range.

Method used

A high-concentration salt solution with strong hydration ability is used as the dispersed phase. By limiting the free movement of water molecules without the need for an external crosslinking agent, the interaction between polymer chains is enhanced, thereby preparing a low-modulus, high-strength and low-mechanical hysteresis flexible conductive hydrogel.

Benefits of technology

It realizes the mechanical properties of the conductive gel without relying on crosslinking agent, and improves the wear comfort of the flexible strain sensor, resistance to external loading and stability of the electrical signal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874976A_ABST
    Figure CN119874976A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of conductive gel, in particular to high-concentration salt-based conductive gel as well as a preparation method and application thereof. By means of the strong hydration capacity of high-concentration salt ions of a dispersed phase in the hydrogel, polymer chains can be spontaneously assembled to form the solid gel with mechanical bearing capacity on the premise of not additionally adding a cross-linking agent, and the prepared gel shows the mechanical property suitable for being applied to a flexible strain sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of conductive gels, in particular to a high-concentration salt-based conductive gel and a preparation method and application thereof, and in particular to a flexible conductive hydrogel which uses a high-concentration salt solution with strong hydration ability as a dispersed phase and has low modulus, high strength and low hysteresis mechanical characteristics, and a preparation method thereof and application thereof in a strain sensor. Background Art

[0002] Flexible strain sensors are flexible electronic devices that can sense the activities of the detected object (commonly seen in deformations such as stretching, bending, twisting, compression, and folding). They are usually composed of conductive materials and flexible polymer substrates. They indirectly record various physical activities of the detected person through changes in electrical parameters such as resistance, capacitance, and current of the flexible strain sensor. Compared with rigid strain sensors based on metal or semiconductor materials, the biggest feature of flexible strain sensors is their large-scale low-actuation deformability. Gel is a new type of material composed of a polymer network with mechanical bearing capacity and a liquid dispersed phase. Gel not only exhibits mechanical properties similar to those of human organs, but also exhibits excellent biocompatibility, an open liquid environment, and good processability, making it an ideal substrate for manufacturing flexible strain sensors. Although gel has large-scale deformation capabilities, mechanical parameters such as modulus, strength, and mechanical hysteresis have a significant impact on the performance of gel-based flexible strain sensors.

[0003] Although ordinary conductive gel strain sensors can convert some physical activities of the detected object into electrical signals, some mechanical parameters of the gel itself fail to meet the use requirements, resulting in unsatisfactory performance of gel-based flexible strain sensors, which are specifically manifested in low signal-to-noise ratio of the output electrical signal, local signal loss, and narrow signal detection threshold range. The modulus of the conductive gel will have a direct impact on the flexibility of the strain sensor. The human organs or tissues being detected generally show a modulus of kPa level, which is common in skin tissue. If the modulus of the gel-based flexible strain sensor is at the MPa level, when the strain sensor is attached to the skin to detect human activities, it will cause two deficiencies due to the mismatch of mechanical modulus. First, it will greatly reduce the wearing comfort of the detected person, and second, the high modulus of the material requires a greater driving force, so slight activities cannot be detected by the strain sensor; the strength of the conductive gel will also have a significant impact on the gel-based flexible strain sensor. Strength is an important mechanical parameter that reflects the material's resistance to external loads. The polymer network The packing density is diluted by the liquid dispersed phase, the polymer network is unevenly distributed, and the shielding effect of the liquid dispersed phase on the supramolecular interactions between polymer chains or within the polymer chains leads to the lower strength of the gel than other materials. If the low-strength conductive gel is used in the strain sensor, it is likely to cause the gel to break during use because of its low ability to resist external loads. The mechanical hysteresis of the gel is due to the destruction of the covalent bonds or supramolecular interactions of the polymer network during the deformation of the gel, which leads to a significant reduction in the stress of the gel during the unloading process. The destroyed structure in each loading-unloading cycle causes the mechanical strength of the gel material to gradually weaken, so the significant mechanical hysteresis will lead to a decrease in the stability and toughness of the sensor. Many articles have reported strategies such as cross-linking, double network, and crystallization to enhance the mechanical properties of conductive hydrogels. These strategies will increase the modulus of the gel while improving the strength of the conductive gel, thereby increasing the driving force required for this type of conductive gel to be used as a strain sensor, which is disadvantageous for the wearer of the strain sensor. In addition, the mechanically enhanced gels through these strategies will be accompanied by the destruction of the mechanical bearing capacity structure during the loading-unloading process, resulting in mechanical hysteresis, strength loss and residual strain, and these mechanical performances will have a negative impact on the performance of gel-based strain sensors. According to the above analysis, in order to prepare gel-based flexible strain sensors with better performance and obtain more stable, reliable and real electrical signals, it is very important to optimize the mechanical properties of gel materials, especially to prepare hydrogel substrates with low modulus, high strength and low mechanical hysteresis.

[0004] In view of this, this invention is proposed. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a high-concentration salt-based conductive gel and a preparation method and application thereof, which is a low-modulus, high-strength and low-mechanical hysteresis flexible conductive hydrogel that relies on a high-concentration salt solution with strong hydration ability as the dispersed phase.

[0006] It should be noted that the present invention provides a high-concentration salt-based conductive gel by relying on a high-concentration salt solution with strong hydration ability as a dispersed phase. It is based on the strong polarization attraction and binding ability of ions formed by the ionization of inorganic salts in the gel to water molecules, so that the free water molecules in the hydrogel dispersed phase are confined to move, and at the same time occupy the thermal motion space of the hydrophilic polymer chain, enhance the interaction between or within the molecular chains, and finally achieve gelation and mechanical enhancement without relying on the addition of an external cross-linking agent.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] In the first aspect, the present invention provides a high-concentration salt-based conductive gel by using a high-concentration salt solution with strong hydration ability as a dispersed phase, which comprises, by weight:

[0009] 5 to 30 parts of polymerizable monomer, 0.1 to 2 parts of thermal initiator, 10 to 70 parts of inorganic salt, and 20 to 80 parts of deionized water.

[0010] In an optional embodiment, the polymerizable monomer is at least selected from one of acrylic acid, hydroxyethyl acrylate, and hydroxybutyl acrylate.

[0011] In an optional embodiment, the thermal initiator is selected from at least one of potassium persulfate (K2S2O8), ammonium persulfate ((NH4)2S2O8), potassium persulfate (K2S2O8) & sodium sulfite (Na2SO3).

[0012] In an optional embodiment, the inorganic salt is at least selected from ferric chloride (FeCl3), ferric nitrate (Fe(NO3)3), magnesium nitrate (Mg(NO3)3), and magnesium bromide (MgBr2).

[0013] In a second aspect, the present invention provides a method for preparing a high-concentration salt-based conductive gel, the method specifically comprising the following steps:

[0014] 1) Preparation of a precursor solution: Mix and dissolve the raw materials of the high-concentration salt-based conductive gel as described in claim 1 to obtain a uniform and transparent precursor solution;

[0015] 2) Thermally initiated polymerization: placing the uniform and transparent precursor solution in a hot environment to undergo polymerization reaction to obtain the high-concentration salt-based conductive gel.

[0016] In an optional embodiment, the thermal environment is a hot water bath or a hot air bath with a temperature of 30 to 70°C.

[0017] In an optional embodiment, the thermally initiated polymerization time is 0.5 to 12 hours.

[0018] In a third aspect, the present invention provides an application of a low modulus, high strength and low mechanical hysteresis flexible conductive hydrogel in a strain sensor that relies on a high concentration salt solution with strong hydration ability as a dispersed phase as described above.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. Traditional synthetic hydrogels need to add crosslinking agents during synthesis to make the polymer chains form a three-dimensional polymer network, while the conductive gel provided by the present invention does not require the addition of crosslinking agents during the preparation process, that is, the hydration capacity of high-concentration ions in the dispersed phase is used to limit the free movement of almost all water molecules, so that the proportion of free water molecules is greatly reduced, thereby reducing the free movement space of the polymer molecular chains, increasing the density of the polymer continuous phase, and also enhancing the interaction between the polymer molecular chains, ultimately enhancing the mechanical properties of the conductive gel.

[0021] 2. The present invention makes use of the strong hydration ability of the high-concentration ions in the hydrogel dispersed phase to enable the synthesized polymer chain network to spontaneously assemble to form a solid gel without relying on a cross-linking agent, and the prepared gel exhibits mechanical properties suitable for the application of flexible strain sensors, specifically: the low modulus mechanical characteristics improve the comfort of the sensor wearer and reduce the driving force required for sensor deformation; the high-strength mechanical characteristics improve the sensor's resistance to external loading damage; the low mechanical hysteresis characteristics enable the flexible strain sensor to ensure the stability of the mechanical properties while ensuring the integrity of the output electrical signal.

[0022] 3. The strong hydration ability of the high concentration ions in the dispersed phase of the conductive hydrogel of the present invention not only enables the linear polymer chains to form a solid polymer gel, but also this special strong hydration of ions optimizes the mechanical properties of the conductive gel. In addition, the migration of ions under an electric field gives the gel excellent ionic conductivity.

[0023] 4. The present invention relies on a high-concentration salt solution with strong hydration ability as the dispersed phase to prepare a low modulus, high strength and low mechanical hysteresis flexible conductive hydrogel using a one-pot method. The preparation process is simple, green, environmentally friendly and low in energy consumption. At the same time, all the raw materials involved are simple and easy to obtain.

[0024] 5. The low modulus, high strength and low mechanical hysteresis flexible conductive hydrogel of the present invention, which relies on a high concentration salt solution with strong hydration ability as the dispersed phase, has high transparency and is easy to observe the real-time state of the object to be detected that is covered by the flexible sensor.

[0025] 6. Since the present invention relies on a high-concentration salt solution with strong hydration ability as the dispersed phase and the synthetic raw material of the low modulus, high strength and low mechanical hysteresis flexible conductive hydrogel does not include a cross-linking agent, the gel prepared by the present invention can be easily recycled. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0027] Figure 1 This is a test diagram of the mechanical properties of the conductive gel prepared by the present invention;

[0028] Figure 2 The electrical signal diagram of the conductive gel prepared by the present invention when used as a strain sensor;

[0029] Figure 3 This is a test diagram of the mechanical properties of the gel prepared in the comparative example of the present invention;

[0030] Figure 4 This is a graph of electrical signals when the gel prepared in the comparative example of the present invention is used as a strain sensor. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.

[0033] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.

[0034] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.

[0035] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.

[0036] The invention discloses a high-concentration salt-based conductive gel and a preparation method and application thereof.

[0037] In a first aspect, this embodiment provides a conductive gel that relies on a high-concentration salt solution with strong hydration ability as a dispersed phase, and the raw materials for preparing the conductive gel include a polymerizable monomer, a thermal initiator, an inorganic salt, and deionized water.

[0038] The high-concentration salt-based conductive gel in this embodiment is prepared by thermally induced free radical polymerization of unsaturated acrylate monomers. The polymer chains are spontaneously formed into solid polymer gels under the influence of the strong hydration ability of ions in the high-concentration salt solution inside the gel. The strong hydration ability of the ions forms a micro-region with water molecules wrapping the ion center, thereby squeezing the free movement space of the polymer chains. The polymer chains with restricted Brownian motion strengthen the interaction between the groups and weaken the shielding and plasticizing effect of water molecules on the polymer chains. Finally, without the help of an external cross-linking agent, a hydrogel with low modulus, high strength and low hysteresis mechanical characteristics is obtained. At the same time, the free positive-valent metal ions and negative-valent counter ions in the gel give the gel ionic conductivity.

[0039] In an optional embodiment, by weight, the polymerizable monomer is 5 to 30 parts, the thermal initiator is 0.1 to 2 parts, the inorganic salt is 10 to 70 parts, and the deionized water is 20 to 80 parts.

[0040] In an optional embodiment, the type of inorganic salt will have a significant impact on the mechanical properties of the final gel, because the hydration capacity of different ions varies greatly. Generally speaking, the smaller the radius and the higher the valence of the ion, the stronger the hydration capacity.

[0041] In an optional embodiment, the concentration of ions will also have an important impact on the mechanical properties of the gel. The higher the concentration of ions, the higher the proportion of bound water molecules, while the proportion of free water molecules decreases, which is more conducive to enhancing the mechanical properties of the gel.

[0042] In an optional embodiment, the polymerizable monomer is selected from at least one of acrylic acid, hydroxyethyl acrylate and hydroxybutyl acrylate.

[0043] In an optional embodiment, the thermal initiator is selected from at least one of potassium persulfate (K2S2O8), ammonium persulfate ((NH4)2S2O8), potassium persulfate (K2S2O8) & sodium sulfite (Na2SO3).

[0044] In an optional embodiment, the inorganic salt includes at least one of ferric chloride (FeCl3), ferric nitrate (Fe(NO3)3), magnesium nitrate (Mg(NO3)3), magnesium bromide (MgBr2) and aluminum chloride (AlCl3).

[0045] In a second aspect, the present invention provides a method for preparing a high-concentration salt-based conductive gel, comprising:

[0046] 1. Preparation of precursor solution: Mix and dissolve the raw materials of the high-concentration salt-based conductive gel described in any of the above embodiments to obtain a uniform and transparent precursor solution;

[0047] 2. Thermally initiated polymerization: placing the uniform and transparent precursor solution in a hot environment to undergo polymerization reaction to obtain a high-concentration salt-based conductive gel.

[0048] In an optional embodiment, the thermal environment is a hot water bath or a hot air bath with a temperature of 30 to 70°C.

[0049] In an optional embodiment, the thermally initiated polymerization time is 0.5 to 12 hours.

[0050] In a third aspect, the present invention provides an application of a low modulus, high strength and low mechanical hysteresis flexible conductive hydrogel in the field of strain sensors that relies on a high-concentration salt solution with strong hydration ability as a dispersed phase as described in any of the aforementioned embodiments.

[0051] In order to make the objectives, technical solutions and benefits of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. The specific conditions not specified in the embodiments are carried out according to conventional conditions or the conditions recommended by the instrument and equipment manufacturers. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0052] Example 1

[0053] This example prepares a low modulus, high strength and low mechanical hysteresis flexible conductive hydrogel that relies on a high concentration salt solution with strong hydration ability as a dispersed phase. The specific process is as follows:

[0054] Weigh 2g of acrylic acid monomer and dissolve it in 7g of deionized water, then add 6g of ferric chloride inorganic salt to dissolve it, and finally add 0.02g of potassium persulfate (K2S2O8) and stir it thoroughly to completely dissolve it to obtain a uniform and transparent precursor solution.

[0055] The uniform and transparent precursor solution is sealed into a transparent mold (glass or acrylic material), and then placed in a hot water bath for thermal polymerization at a water bath temperature of 40°C for 5 hours. Finally, the mold is demolded to obtain a high-concentration salt-based conductive gel.

[0056] Test Example 1

[0057] The dosage of the inorganic ferric chloride salt in Example 1 was adjusted to 0 g, 2 g, 4 g and 6 g, and the mechanical properties of the prepared hydrogel were evaluated using a universal material mechanics tester. The detection method is shown in GB / T 1040.1-2018, and the test results are shown in Figure 1 .

[0058] like Figure 1 As shown in the tensile stress-strain curve, it can be seen that in the embodiment of the present invention, when the mass of ferric chloride in the gel is 6g, the modulus of the prepared low modulus, high strength and zero mechanical hysteresis flexible conductive hydrogel is as low as 83kPa, the strength is 1.8MPa, and the dissipated energy in the loading-unloading cycle at the maximum strain of 200% is only 27kJ / m 3 .

[0059] Test Example 2

[0060] The ionic conductivity of the hydrogel prepared in Example 1 was measured using an electrochemical workstation using an alternating current impedance method.

[0061] The conductivity test results show that as the amount of inorganic salt ferric chloride increases, the ionic conductivity of the conductive gel also increases. When the mass of inorganic salt ferric chloride is 6g, the ionic conductivity of the conductive gel is 6.5S / m. For the sample without ferric chloride inorganic salt, since it does not contain iron ions and chloride ions, its conductivity is very low.

[0062] Test Example 3

[0063] The performance of the hydrogel prepared in Example 1 as a strain sensor was tested using a digital source meter. When the strain sensor was loaded with the same weight and subjected to a cyclic loading-unloading test, the resistance signal change of the conductive gel strain sensor was tested. The test results are detailed in Figure 2.

[0064] like Figure 2 As shown in the figure, thanks to the low mechanical hysteresis of the gel, the electrical signal output by the sensor has good repeatability and stability. This is because the low mechanical hysteresis of the conductive gel enables the material to maintain mechanical stability during the cyclic loading-unloading process, that is, the same load can correspond to the same deformation of the gel.

[0065] The experimental results of the above test examples 1 to 3 show that the flexible conductive hydrogel of the present invention, which relies on a high-concentration salt solution with strong hydration ability as a dispersed phase, has high mechanical strength, low modulus and low mechanical hysteresis characteristics. The addition of ferric chloride inorganic salt not only improves the mechanical properties of the gel, but also gives the gel good ionic conductivity. Benefiting from the excellent mechanical properties of the gel, the low modulus, high strength and low mechanical hysteresis flexible conductive hydrogel-based strain sensor has the advantages of stable signal, strong resistance to damage and low driving force.

[0066] Example 2

[0067] This embodiment prepares a high-concentration salt-based conductive gel that relies on a high-concentration salt solution with strong hydration ability as a dispersed phase. The main difference from Example 1 is that the inorganic salt of ferric chloride is replaced by an inorganic salt of magnesium nitrate.

[0068] The flexible conductive hydrogel prepared in this example has a modulus of 126 kPa, a strength of 1.7 MPa, and a dissipated energy of 48 kJ / m in a loading-unloading cycle at a maximum strain of 200%. 3 , the maximum ionic conductivity is 4.2S / m.

[0069] Example 3

[0070] This embodiment prepares a high-concentration salt-based conductive gel that relies on a high-concentration salt solution with strong hydration ability as a dispersed phase. The main difference from Example 1 is that the polymerizable acrylic acid is replaced with an equal mass fraction of hydroxyethyl acrylate monomer.

[0071] The flexible conductive hydrogel prepared in this example has a modulus of 52 kPa, a strength of 1.5 MPa, and a dissipated energy of 58 kJ / m in a loading-unloading cycle at a maximum strain of 200%. 3 , the maximum ionic conductivity is 4.1S / m.

[0072] Example 4

[0073] This embodiment prepares a high-concentration salt-based conductive gel. The main difference from Example 1 is that the thermal initiator potassium persulfate (K2S2O8) is replaced by an oxidation-reduction initiator system of potassium persulfate (K2S2O8) & sodium sulfite (Na2SO3) in equal parts by mass, and the molar ratio of potassium persulfate to sodium sulfite is 1:1.

[0074] The flexible conductive hydrogel prepared in this embodiment has a modulus of 123 kPa, a strength of 1.4 MPa, and a dissipated energy of 45 kJ / m in a loading-unloading cycle at a maximum strain of 200%. 3 , the maximum ionic conductivity is 5.7S / m.

[0075] In order to further demonstrate the beneficial effects of the present invention and to better understand the present invention, the following comparative examples are used to further illustrate the technical features disclosed in the present invention, but they should not be construed as limiting the present invention. Other improvements made by those skilled in the art based on the above invention content without inventive work are also considered to fall within the scope of protection of the present invention.

[0076] Comparative Example 1

[0077] This comparative example prepares a conductive hydrogel, which is mainly different from Example 1 in that the inorganic salt of ferric chloride is completely replaced by an inorganic salt of sodium chloride with a very weak hydration ability in the same mass fraction.

[0078] The material prepared in this comparative example cannot form a solid hydrogel because the ion hydration capacity in the sodium chloride inorganic salt aqueous solution is very weak, and the acrylamide monomer cannot be spontaneously polymerized to form a solid hydrogel without the aid of an external crosslinking agent.

[0079] Comparative Example 2

[0080] This comparative example prepared a conductive hydrogel. The main difference from Example 1 is that a 30 mg / mL agarose solution was added to the polymerizable precursor solution to construct a hydrogel with a double network chemical structure, and a control gel sample with high modulus and significant mechanical hysteresis was obtained. The mechanical properties are detailed in Figure 3 , the strain sensor electrical signal is detailed in Figure 4 .

[0081] like Figure 3 As shown, the modulus of the conductive hydrogel prepared in this comparative example is 865 kPa, the maximum breaking strength is 3.4 MPa, and the dissipated energy in the loading-unloading cycle at the maximum strain of 200% is 7089 kJ / m 3 , the maximum ionic conductivity is 5.1S / m. Figure 4 As shown, since the control double-network structure conductive gel has a large mechanical modulus and obvious mechanical hysteresis, the electrical signal obtained by the sensor is unstable.

[0082] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A high concentration salt-based conductive gel, characterized in that: The conductive gel comprises, by weight: 5 to 30 parts of polymerizable monomer, 0.1 to 2 parts of thermal initiator, 10 to 70 parts of inorganic salt, and 20 to 80 parts of deionized water.

2. The high-concentration salt-based conductive gel according to claim 1, characterized in that: The polymerizable monomer is at least one selected from acrylic acid, hydroxyethyl acrylate and hydroxybutyl acrylate.

3. The high concentration salt-based conductive gel according to claim 1, characterized in that: The thermal initiator is selected from at least one of potassium persulfate (K2S2O8), ammonium persulfate ((NH4)2S2O8), potassium persulfate (K2S2O8) & sodium sulfite (Na2SO3).

4. The high-concentration salt-based conductive gel according to claim 1, characterized in that: The inorganic salt is at least one selected from ferric chloride (FeCl3), ferric nitrate (Fe(NO3)3), magnesium nitrate (Mg(NO3)3), and magnesium bromide (MgBr2).

5. A method for preparing a high-concentration salt-based conductive gel as claimed in claim 1, characterized in that: The method specifically comprises the following steps: 1) Preparation of a precursor solution: Mix and dissolve the raw materials of the high-concentration salt-based conductive gel as described in claim 1 to obtain a uniform and transparent precursor solution; 2) Thermally initiated polymerization: placing the uniform and transparent precursor solution in a hot environment to undergo polymerization reaction to obtain the high-concentration salt-based conductive gel.

6. The method for preparing a high-concentration salt-based conductive gel according to claim 5, characterized in that: The thermal environment is a hot water bath or a hot air bath with a temperature of 30-70°C.

7. The method for preparing a high-concentration salt-based conductive gel according to claim 5 or 6, characterized in that: The thermally initiated polymerization time is 0.5 to 12 hours.

8. Use of the high-concentration salt-based conductive gel as claimed in claim 1 or the high-concentration salt-based conductive gel prepared by the method as claimed in claim 5 in a strain sensor.